2020
DOI: 10.1177/0011000020954534
|View full text |Cite
|
Sign up to set email alerts
|

Sexist Microaggressions: Traumatic Stressors Mediated by Self-Compassion

Abstract: Women regularly endure sexist microaggressions, which are often associated with anger, depression, anxiety, low self-esteem, and trauma. The cumulative effects of sexist microaggressions may result in internalized sexism and undermine self-compassion. Notably, prolonged exposure to sexism is associated with trauma symptoms; however, the traumatic effects of sexist microaggressions have remained largely theoretical. Thus, we examined the role of sexist microaggressions as a traumatic stressor and evaluated self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The potential homogeneity of experiences of racism in this sample of African Americans might have contributed to individual racism not being a significant predictor, whereas classism and the interaction term were. Identity development may also influence individuals’ ability to perceive and name their discriminatory experiences, serving as a moderator (Cherry & Wilcox, 2021; Diemer et al, 2006). Further, our sample had more resources (i.e., they could access a computer and the internet), and likely had more privilege that allowed them to engage in conscientization —being aware of oppression, and thus more likely to report it.…”
Section: Discussionmentioning
confidence: 99%
“…The potential homogeneity of experiences of racism in this sample of African Americans might have contributed to individual racism not being a significant predictor, whereas classism and the interaction term were. Identity development may also influence individuals’ ability to perceive and name their discriminatory experiences, serving as a moderator (Cherry & Wilcox, 2021; Diemer et al, 2006). Further, our sample had more resources (i.e., they could access a computer and the internet), and likely had more privilege that allowed them to engage in conscientization —being aware of oppression, and thus more likely to report it.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among a sample of undergraduate women, Gartner (2019) found that experiences with gender microaggressions were significantly and positively related to depressive and posttraumatic symptoms. In another example among 370 adult cis-gender women, Cherry and Wilcox (2021) found sexist microaggressions positively predicted trauma symptomology, and this association was partially mediated by selfcompassion. In the current study, we were interested in exploring the link between gender microaggressions and depressive symptoms, which has implications for active-duty women's mental health as well as unit cohesion, morale, mission readiness, and performance (Armistead-Jehle et al, 2011;Gaddes et al, 2017;Pflanz & Ogle, 2006).…”
Section: Gender Microaggressions: a Form Of Covert Discriminationmentioning
confidence: 93%
“…Although researchers have addressed how women experience overt sexual harassment and gender discrimination in the military (Bell et al, 2018; Breslin et al, 2019), far less research has been conducted on covert forms of discrimination in this context. In the current study, we were interested in one form of covert discrimination in the U.S. military—gender microaggressions that target self-identified women (also referred to as sexist microaggressions; Cherry & Wilcox, 2021). Scholars have addressed gender microaggressions in a variety of contexts, such as undergraduate education (Gartner, 2021), medical school (Struble et al, 2022), and the workplace (Basford et al, 2014).…”
Section: Gender Microaggressions: a Form Of Covert Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence suggests that the cumulative effects (both recent and lifetime) of microaggressions are significantly associated with traumatic stress symptoms. However, most studies have focused on race or gender and do not account for the gendered racial microaggressions of women of color (Abdullah et al, 2021; Cherry & Wilcox, 2021; Torres & Taknint, 2015). Only a few studies have explored the link between gendered racial microaggressions and trauma and have found that Black women who experience greater gendered racial microaggressions also report greater traumatic stress (Dale & Safren, 2019; Moody & Lewis, 2019; Sharma & Dale, 2022; Sissoko et al, 2022; Watson & Henderson, 2022).…”
Section: Discrimination and Traumatic Stressmentioning
confidence: 99%